Penggunaan Data Satelit Untuk Pemodelan Hidrologi Dan Analisis Banjir Di Sub-DAS Rokan Stasiun Lubuk Bendahara - Handayani, Yohanna Lilis; Karunia, Ariani; Sutikno, Sigit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Many rules were did to overcome flood problem which one to use remote sensing in hydrological modeling with data-based satellite. This research conduct hydrological modeling using satellite data with Integrated Flood Analysis System (IFAS) version 1.3.0 for the analysis of the flood discharge at the sub-watershed Rokan Hulu at AWLR Lubuk Bendahara Station. Satellite data of hidrological modeling was the data in February 2012. The rainfall satellite data are used GSMaP_NRT original and corrected in the form of rainfall data hourly. The parameters used to assess the accuracy of the model is wave shape error (Ew), volume error (Ev), and peak discharge error (Ep). To get a percentage of a small error was did calibration parameters IFAS. The result of calibration Ew, Ev, and Ep are Â 9,58%, 17,28%, and Ep 10,81% for GSMaP_NRT original. The results of GSMaP_NRT corrected are 134,94%, 101,89%, and 18,37% . Â Keywords : hydrological modeling, flood analysis, satellite data, IFAS, calibration